Integrating climate-smart practices in forestry: insights from Europe and America - Xie, Hongtao; Chang, Mengyuan; Wang, G. Geoff; Tang, Yu; Jin, Songheng (Frontiers in Plant Science, 2025)
Global climate change poses a great obstacle to the sustainability of world forestry, and the trifecta of enhancing forest stock, minimizing greenhouse gas emissions, and attaining sustainable forest management is still challenging. Climate-smart forestry (CSF), however, offers promising solutions to these issues, with its core objective being to foster sustainable development through enhanced forest resilience, reduced greenhouse gas emissions, and boosted forest productivity and income. This emerging focus on CSF seeks to understand the mechanisms of interactions between forest ecosystems and climate change and eventually find locally acceptable solutions. This review delves into the developmental objectives of CSF, providing a new insight into the latest research advances and practical experience in CSF among eight Europe and American countries, including Brazil, USA, Czech, Finland, etc. Meanwhile, we identify the main challenges that CSF is facing currently, including the climate change uncertainty, disconnection among policy, science, and practice, and trade-offs between different CSF objectives. To address these challenges, we proposed five potential aspects for CSF development and sketched their main applications. Specifically, Technological innovation and digital applications are highly encouraged, including GIS and remote sensing, Internet of Things (IoT), and artificial intelligence technologies. Besides, Intelligent logging operations and wood processing, forest bioeconomy should also be considered to promote the CSF development. The results offer new perspectives and strategies for mitigating climate change via sustainable forestry management and protecting forest economies and communities in the context of accelerated global climate change.